Vibration of mechanical and structural systems with microcomputer applications - James, M. L.; Smith, G.M.;Wolford, J.C.;Whaley, P.W. (New York : Harper & Row Publishers, Inc., 1994)
The purpsoe of this text is to present comprehensive coverage of the fundamental principles of vibration theory, with emphasis on the application of these principles to practical engineering problems.
Basic concepts/mathematics -- Free vibration of single-degree-of-freedom- systems -- Harmonic excitation of single-degree-of-freedom systems -- transient vibration from nonharmonic excitation -- Free vibration of multiple-degree-of-freedom systems (discrete and lumped-mass systems) -- Forced vibration of discrete and lumped-mass systems/modal analysis -- Lagrange's equations and the finite-element method in vibration analysis -- Continuous systems
Includes index.
Keywords: VIBRATION